1989
DOI: 10.1136/bmj.298.6678.931
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone cream for cyclic breast pain.

Abstract: erythrocytes. It is partly explained by acute phase increases in plasma fibrinogen concentration and viscosity. In particular, however, we found that the filterability of both polymorphonuclear and mononuclear leucocytes is reduced in acute cerebral infarction. This may not only explain the reduced filterability of blood but also promote malperfusion of the microcirculation and infarction.Reduced filterability of leucocytes may be part of the acute phase response to injury, as suggested by the correlation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 4 publications
(1 reference statement)
0
8
0
1
Order By: Relevance
“…175 Progesterone cream applied to the breast was not better than placebo for cyclic breast pain in another small randomized study. 176 Danazol and Gestrinone.-Danazol, the only medication approved by the Food and Drug Administration for treatment of mastalgia, is a derivative of 17-α-ethinyl testosterone that suppresses gonadotropin secretion, prevents luteinizing hormone surge, and inhibits ovarian steroid formation. Danazol relieves breast pain and tenderness in controlled clinical trials.…”
Section: Hormonally Active Medicationsmentioning
confidence: 99%
“…175 Progesterone cream applied to the breast was not better than placebo for cyclic breast pain in another small randomized study. 176 Danazol and Gestrinone.-Danazol, the only medication approved by the Food and Drug Administration for treatment of mastalgia, is a derivative of 17-α-ethinyl testosterone that suppresses gonadotropin secretion, prevents luteinizing hormone surge, and inhibits ovarian steroid formation. Danazol relieves breast pain and tenderness in controlled clinical trials.…”
Section: Hormonally Active Medicationsmentioning
confidence: 99%
“…Recently this type of fibrocystic breast disease and mastalgia treatment was very common in France. Some random control "cross-over" studies did not find such a significant improvement with this type of the therapy versus placebo group [32]. However, in double blind study in Italy it was noted that the use of micronized progesterone vaginal cream decreased breast pain by 64.9% in patients with mastalgia versus 22% in control group [33].…”
Section: Discussionmentioning
confidence: 95%
“…McFadyen et al found that progesterone cream applied locally was no better than placebo cream in relieving mastalgia. 63 Along similar lines, a small, randomized, double-blind crossover study (N = 26) by Maddox et al concluded that the therapeutic response of 20 mg/day of oral medroxyprogesterone acetate during the luteal phase was no better than a placebo in the management of cyclic mastalgia. 64 However, in a randomized, double-blind, placebo-controlled study conducted in Italy by Nappi et al, a vaginal cream of micronized progesterone was found to be effective in reducing pain in 64.9% of cases, compared with 22.2% of controls.…”
Section: Progesteronementioning
confidence: 95%